Visceral obesity and insulin resistance associate with CD36 deletion in lymphatic endothelial cells - Vincenza Cifarelli (Nature Portfolio, 2021)
Genetic variants in CD36 have been associated with metabolic syndrome. Here, the authors found that lymphatic vessel integrity and lipid transport are influenced by CD36 expression, and lymphatic endothelial cell CD36 deficiency causes visceral obesity and insulin resistance, which are risk factors for metabolic syndrome and diabetes.